256 DRAINAGE OF ANASTOMOTIC LEAKAGE AFTER ESOPHAGECTOMY: THROUGH THE FISTULA OR NOT, WHICH IS BETTER?. (14th September 2020) - Dai, L; Zhao, X; Yang, Y; Fu, H; Chen, K
Abstract: : Thoracic abscess and/or mediastinal abscess due to anastomotic leakage after esophagectomy are very serious postoperative complications, and adequate surgical drainage is of critical importance to treatment. In this study, we compared the treatment efficacies of two drainage methods (through-the-fistula or not-through-the-fistula). Methods: We retrospectively collected the esophageal cancer patients who underwent surgery from Jan 2016 to Aug 2019 who had complications of anastomotic leakage which was above grade III according to Lerut grading system. The drainage methods of thoracic/mediastinal abscess were drainage tube through-the-fistula (TF) (with the aid of X-ray or endoscope) and not-through-the-fistula (nTF) (via thorax or neck). According to the time from drainage tube placed to stable of the fistula, the patients were divided into fast stable group (<14 days) and slow stable group (≥14 days), and the differences of clinical characteristics and drainage methods were compared. Results: Among the 495 cases underwent surgery, 43 (8.7%) had anastomotic leakage, 20 (4.0%) of which were grade III. 8 obtained fast stable and 12 were slow stable. As to drainage efficacy, there were 87.5% and 16.7% of the cases adopted TF drainage in fast stable group and slow stable group, respectively (P = 0.002). As to safety, there were 1 case in TF group that needed repeated drainage, whereas in nTF group, there were 2 cases died of bleeding and 2 cases needed repeated drainage (P = 0.319). Furthermore, there were 2 residual cavity cases after recovery in the nTF group. Conclusion: TF drainage is safe and reliable for the thoracic/mediastinal abscess caused by anastomotic leakage after esophagectomy, which was better compared to nTF drainage, and facilitated recovery of the anastomosis.